Physical Properties of Emulsion-Based Hydroxypropyl Methylcellulose/Whey Protein Isolate (Hpmc/Wpi) Edible Films - Osorio-Lira, F (Elsevier Ltd, 2015)
The objective of this research was to study the effect of the film microstructure of oil-in-water emulsions stabilized by hydroxypropyl methyl cellulose/whey protein isolate (HPMC/WPI) with or without sodium dodecyl sulfate (SDS) over physical properties of HPMC/WPI emulsion-based films. The films were prepared with different HPMC/WPI-oil-SDS combinations (%w/w for 100 g of dispersion): HPMC; WPI; HPMC/1WPI-0.5-SDS; HPMC/1WPI-1; HPMC/2WPI-0.5; HPMC/2WPI-1-SDS. Physical properties of films were evaluated. The results showed no statistical differences (p > 0.05) between the thicknesses of EFs (0.156 ± 0.004 mm). The effect of oil content and incorporation of SDS showed the inverse trend for WI and ΔE, the increasing order of change, for WI and ΔE, among the formulation evaluated was: HPMC/1WPI-1 > HPMC/2WPI-0.5 > HPMC/2WPI-1.0-SDS ≈ HPMC/1WPI-0.5-SDS ≈ WPI > HPMC for WI and HPMC/1WPI-0.5-SDS > HPMC/2WPI-1.0-SDS > HPMC/2WPI-0.5 > HPMC/1WPI-1 for ΔE, respectively. The addition of oil and SDS decreased the TS and EB, because oil addition into EF induces the development of structural discontinuities, producing an EF with less chain mobility, and consequently, with less flexibility and resistance to fracture. © 2015 Elsevier Ltd. All rights reserved.